Case report: Traumatic lumbosacral spondyloptosis with locked L5 inferior articular process - Tang, Tao; Liu, Yuchi; Cao, Jian; Wu, Tianlong; He, Dingwen; Cheng, Xigao; Xie, Shuihua (Frontiers in Surgery, 2023)
Background Traumatic lumbosacral spondyloptosis is a very rare spinal disease caused by high-energy trauma. We report a case of traumatic lumbosacral spondyloptosis with locked L5 inferior articular process. Case presentation A 33-year-old man presented with multisite pain for 6 h following waist trauma and was admitted to the hospital. He suffered multiple injuries from severe impact on the waist after driving an out of control forklift truck. Preoperative imaging examinations revealed that the patient was diagnosed with traumatic lumbosacral spondyloptosis and the L5 inferior articular process was locked into the anterior margin of the S1 vertebra. A posterior instrumentation, decompression of the cauda equina, and interbody fusion procedure was performed. The patient received hyperbaric oxygen and rehabilitation treatment 10 days after the surgery. At the 6-month postoperative follow-up, the muscle strength of the lower limbs was improved, the patient had no numbness of both lower limbs, and the urinary retention symptom was significantly improved. The American Spinal Injury Association grade improved from grade C preoperatively to grade D postoperatively. As far as we know, there have been no relevant reports on traumatic lumbosacral spondyloptosis with locked L5 inferior articular process yet. Conclusion We believe that the hyperflexion and shear forces were the potential causes of this injury. In addition, the preoperative imaging examinations should be evaluated carefully. If the inferior articular process of L5 were locked, we suggest removing the bilateral inferior articular processes first and then perform reduction.